2019
DOI: 10.1093/nar/gkz409
|View full text |Cite
|
Sign up to set email alerts
|

Delicate structural coordination of the Severe Acute Respiratory Syndrome coronavirus Nsp13 upon ATP hydrolysis

Abstract: To date, an effective therapeutic treatment that confers strong attenuation toward coronaviruses (CoVs) remains elusive. Of all the potential drug targets, the helicase of CoVs is considered to be one of the most important. Here, we first present the structure of the full-length Nsp13 helicase of SARS-CoV (SARS-Nsp13) and investigate the structural coordination of its five domains and how these contribute to its translocation and unwinding activity. A translocation model is proposed for the Upf1-like helicase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
405
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(432 citation statements)
references
References 30 publications
6
405
5
1
Order By: Relevance
“…Cofactor with nsp7 and nsp12, primase [28][29][30] nsp9 Dimerization and RNA binding 31,32 nsp10 Scaffold protein for nsp14 and nsp16 [33][34][35][36] nsp11 Unknown 37 nsp12 Primer dependent RdRp 28,38,39 nsp13 RNA helicase, 5′ triphosphatase [40][41][42] nsp14 Exoribonuclease, N7-MTase 12,[43][44][45] nsp15 Endoribonuclease, evasion of dsRNA sensors [46][47][48] nsp16 2′-O-MTase; avoiding MDA5 recognition, negatively regulating innate immunity 34,35,49 Abbreviations: 3CL pro , chymotrypsin-like protease; DMV, double-membrane vesicle; dsRNA, double-stranded RNA viruses; IFN, interferon; mRNA, messenger RNA; M pro , main protease.…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Cofactor with nsp7 and nsp12, primase [28][29][30] nsp9 Dimerization and RNA binding 31,32 nsp10 Scaffold protein for nsp14 and nsp16 [33][34][35][36] nsp11 Unknown 37 nsp12 Primer dependent RdRp 28,38,39 nsp13 RNA helicase, 5′ triphosphatase [40][41][42] nsp14 Exoribonuclease, N7-MTase 12,[43][44][45] nsp15 Endoribonuclease, evasion of dsRNA sensors [46][47][48] nsp16 2′-O-MTase; avoiding MDA5 recognition, negatively regulating innate immunity 34,35,49 Abbreviations: 3CL pro , chymotrypsin-like protease; DMV, double-membrane vesicle; dsRNA, double-stranded RNA viruses; IFN, interferon; mRNA, messenger RNA; M pro , main protease.…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Eventually, a conformational change in the helicase is caused upon ATP binding. Upon ATP hydrolysis and/or ADP and phosphate release, the helicase relaxes to the initial conformation, resulting in coordinated domain opening and translocation of the helicase 56 . Therefore, the closed state of helicase is populated upon ATP binding, and the open state is populated when the ATPase products dissociate.…”
Section: Discussionmentioning
confidence: 99%
“…This helicase contains a 19-20 loop on 1A domain, which is primarily responsible for its unwinding activity. Furthermore, the study revealed an important interaction of Nsp12 with Nsp13 that further enhances its helicase activity [153].…”
Section: Sars-cov-2 Nsp12 Protein Has a Highly Conserved C-terminal Rmentioning
confidence: 95%
“…Recombinant viral helicase expressed in E.coli Rosetta 2 strain was reported to unwind ~280 bp per second [152]. Figure 30D represents a 2.8 Å X-ray crystal structure of Human SARS Nsp13 (PDB ID: 6JYT) [153]. This helicase contains a 19-20 loop on 1A domain, which is primarily responsible for its unwinding activity.…”
Section: Sars-cov-2 Nsp12 Protein Has a Highly Conserved C-terminal Rmentioning
confidence: 99%